Study of Ibn Katsir's Tafsir on the Values of Patience in QS Al-Anfal: 65, Ar-Ra'du: 22, and An-Nahl: 42 - Abdul Majid; Andri Nirwana AN (al-Afkar, Journal For Islamic Studies, 2024)
The Qur'an is a source of knowledge and teachings revealed by Allah to his creation. In the Qur'an there are many benefits, such as inviting people to pay attention to the value of patience. There are still many cases that occur due to lack of patience. Researchers used the literature review method. The value of patience in question is being patient in facing other humans. Researchers use Ibn Kathir's interpretation. As a result, researchers found the value of patience as stated in Surah Al-Anfal: 65, Ar-Ra'du: 22, and An-Nahl: 42. In essence, Allah SWT commands His servants to get what they want both in this world and in the afterlife through prayer and patience